Ethics, equity and community development - Banks, Sarah; Westoby, Peter (Bristol : Policy Press, 2019)
Drawing on theory and a range of cross-disciplinary and international perspectives, this book examines the place of ethics and ethical practice in community and development across a global spectrum of political, ecological and economic contexts.
pt. 1 The ethico-political context -- One. Ethics, equity and community development: mapping the terrain / Sarah Banks -- Two. Community development in an unequal world: challenging neo-liberal values / Keith Popple -- pt. 2 Everyday ethics in community development practice -- Three. Negotiating roles and boundaries: ethical challenges in community work / Neil Barringham -- Four. Negotiating consent in neighbourhood-based community development work / Mike de Kreek -- Five. Whose ethics counts? Ethical issues in community development and action research with communities facing stigmatisation / Sowmyaa Bharadwaj -- Six. Koorliny birniny, ni, quoppa katatjin: respect and ethics in working with Indigenous Australian communities / Dave Palmer -- Seven. Corporate social responsibility and community development in a mining region in India: issues of power, control and co-option / Bipin Jojo -- pt. 3 Envisioning an ethical space for community development -- Eight. Relational ethics and transformative community organising in the neo-liberal US context / Loretta Pyles -- Nine. A Community Economies perspective for ethical community development / Cradon Diprose -- Ten. Concluding reflections: philosophical perspectives on community and community development / Peter Westoby.
Title from publisher's bibliographic system (viewed on 07 Apr 2022).
Keywords: Community development -- Moral and ethical aspects; Social justice; Electronic books